Normativas para implantação do sistema fotovoltaico e estudo de viabilidade econômica em residência e órgão público municipal - Limberger, Lorivo (2022)
In this dissertation, the legal procedures required for the implementation and regularization of Electric Power Generation through the Photovoltaic System in the State of Paraná were analyzed and presented in a simplified way. Among which the Environmental Licensing and procedures for approval and injection of electricity in the concessionaire in the State of Paraná. In Environmental Licensing, the licensing agency is the Water and Land Institute – IAT, which has legal attributions for the licensing of this activity in the State of Paraná. In the administrative procedures required for the injection contract in the distributed generation electricity grid, the regulations of ANEEL and COPEL, which are currently necessary for the effective contract with the company, were addressed in relation to the prior requirements for the release and after installation of the equipment, the necessary procedures for the approval and operation of the photovoltaic system. Regarding the case studies, a study of the economic feasibility of a residence in the city of Toledo and in relation to a municipal Public Agency was carried out. photovoltaic plant, showing the time for the payback of these units. One of the tools for analyzing the economic feasibility of projects is the payback (rate of return on investment). In a simplified and practical way, the regulatory standards in force were addressed, meeting the demand for knowledge currently by consumers, entrepreneurs and scholars in the sector, for the use of the photovoltaic system.